Examining the Relationship between Microteaching Achievement and Teaching Practicum Performance: An Ex Post Facto Study in Fashion Education Students - Adinda Wibowo; Sri Endah Wahyuningsih (Jurnal Penelitian Pendidikan, 2026)
The assumption that achievement in microteaching directly translates into effective teaching practice performance remains widely accepted in teacher education, yet empirical evidence, particularly in vocational contexts such as fashion education, remains limited and inconclusive. This study aims to examine the relationship between microteaching achievement and teaching practice performance among preservice teachers in fashion education. Employing a quantitative approach with an ex post facto correlational design, the study involved 33 students selected through total sampling. Data were collected from institutional academic records and analyzed using descriptive statistics, normality testing, and Spearman's rho correlation. The results indicate that both microteaching achievement and teaching practice performance are in the high category with low variability; however, the correlation between the two variables is not strong enough to suggest a direct or linear relationship. These findings imply that competencies developed in simulated teaching environments do not automatically transfer to authentic classroom contexts, particularly in vocational education that requires the integration of technical and pedagogical skills. The study highlights the need to redesign microteaching to be more contextually authentic and aligned with real teaching demands, thereby contributing to the improvement of teacher education programs and the development of more adaptive and context-sensitive teaching competencies.